Promoting Farmer Producer organisations in India: A Prosperity Potential for Smallholders - Archana et al. (Indian Journal of Political Science)
The agriculture sector in India is undergoing substantial reforms to compensate for the neglect since economic reforms after 1991. Farmer Producer Organisatons(FPOs), an amalgamation of the existing cooperative model and the private companies, is a collective organisation that has been recently a buzzword in the policy-making corridors. The government of India has articulated an ecosystem of institutional and regulatory reforms to facilitate a better environment for FPOs growth and enhanced income for its members. This paper discusses the various initiatives and opportunities in the form of schemes, policies, and incentives devised by the government to smoothen the flourishing of FPOs. - Reproduced
Keywords: farmer producer organisations, agriculture produce, reforms, acts, marketing